2003
DOI: 10.1007/s00013-003-4659-3
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric continuous Reinhardt domains

Abstract: We extend the concept of Reinhardt domains to complex function spaces and we give a complete parametric description of all bounded symmetric Reinhardt domains in a C 0 -space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In [17] we have shown that a symmetric CRD is a continuous mixture of finite-dimensional Euclidean balls, essentially more involved than direct sums of topological products of balls. In [7] we found matrix representations for linear isomorphisms between two symmetric CRDs.…”
Section: By Definition a Crd Is A Bounded Complete Reinhardt Domain mentioning
confidence: 99%
See 1 more Smart Citation
“…In [17] we have shown that a symmetric CRD is a continuous mixture of finite-dimensional Euclidean balls, essentially more involved than direct sums of topological products of balls. In [7] we found matrix representations for linear isomorphisms between two symmetric CRDs.…”
Section: By Definition a Crd Is A Bounded Complete Reinhardt Domain mentioning
confidence: 99%
“…Later on several authors investigated holomorphic equivalence of generalized Reinhardt domains in atomic Banach lattices [1,2,12]. Motivated by an interesting work of Vigué [19] on the possible lack of symmetry of continuous products of discs with different radii, in [17] we introduced the concept of continuous Reinhardt domains (CRD for short).…”
Section: Introduction a Classical Complete Reinhardt Domain Is An Openmentioning
confidence: 99%
“…These are open subsets of C 0 (Ω), satisfying some additional properties (cf. [18]). In [18] we were led, at some technical point, to study projections with one-dimensional range and additional norm property, which is called bicircularity.…”
Section: Introductionmentioning
confidence: 99%
“…[18]). In [18] we were led, at some technical point, to study projections with one-dimensional range and additional norm property, which is called bicircularity. What we needed to show was that their kernels are Hilbert spaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation